1976
DOI: 10.2307/350418
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reference Group, Perceived Reference Group Permissiveness, and Personal Permissiveness Attitudes and Behavior: A Study of Two Consecutive Panels (1967-1971; 1970-1974)

Abstract: the last month). The proportion o f students reporting homosexual experiences did not differ significantly according to student's race, religion, or region of residencc. The students currently engaged in homosexual activities were more likely than werc other students to approve of extramarital sex, "wife swapping," and group sexual activities. although the majority of students in both groups disapproved of these practices. Small, but significant. positive relationships werc found between frequency of homosexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…66-7) argue that studies by Bell and Chaskes (1970) and Robinson, King, and Balswick (1972) also support it. However, Heltsley and Broderick (1969), Maranell, Dodder, and Mitchell (1970), Middendorp, Brinkman, and Koomen (1970), Walsh, Ferrell, and Tolone (1976), Libby, Gray, and White (1978), and Thornton and Camburn (1987) each fail to support it. See Clayton and Bokemeier (1980) for an excellent review of this literature.…”
Section: Discussionmentioning
confidence: 95%
“…66-7) argue that studies by Bell and Chaskes (1970) and Robinson, King, and Balswick (1972) also support it. However, Heltsley and Broderick (1969), Maranell, Dodder, and Mitchell (1970), Middendorp, Brinkman, and Koomen (1970), Walsh, Ferrell, and Tolone (1976), Libby, Gray, and White (1978), and Thornton and Camburn (1987) each fail to support it. See Clayton and Bokemeier (1980) for an excellent review of this literature.…”
Section: Discussionmentioning
confidence: 95%
“…However, both attitudes towards premarital sex and sexual behavior are reported to be associated with sociodemographic variables. For example, the change from parent to peer orientation, which increases with age of college students, is reported to result in increased sexual permissiveness (Walsh et al, 1976), which in turn is associated with increased rates of premarital sex. At the same time, the proportion of sexually experienced young women is reported to increase with age of the respondent (Zelnik and Kantner, 1977).…”
Section: Multivariate Analysismentioning
confidence: 98%
“…Adolescents, being unable to verify what they perceive, would be influenced by their perceptions. For instance, a longitudinal study (Walsh, Ferrell, & Tolone, 1976) that employed two sequential and partially overlapping panels of college freshmen showed that, in both panels, the perception of sexual permissiveness of their peers at a later time, which exceeded that perceived at an earlier time, was related to a significant increase in respondents’ permissiveness in premarital sexual attitudes and behavior. In addition, Reiss (1967) pointed out that an adolescent’s perception of the sexual attitudes held by his or her close friends was, relative to the adolescent’s perception of the attitudes held by either parent, a better predictor of that adolescent’s own sexual attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%